IMPLEMENTING THE FLIPPED CLASSROOM MODEL IN ACCOUNTING EDUCATION - Moneva, Iva (E-Journal VFU, 2025)
The article introduces the concept of the flipped classroom as an innovative educational model applicable to university-level accounting, with a particular focus on corporate sustainability and ESG reporting. This model transforms the traditional teaching structure by shifting the acquisition of theoretical knowledge to students’ independent preparation, while in-person sessions are dedicated to discussions, case studies, and practical application. The main highlights of the material include the stages of the learning process, presented through a learning path, a SWOT analysis of the model, and its specific implementation within accounting education.
Keywords: flipped classroom; аccounting еducation